The Effect of Rabdosia rubescens on Radiotherapy-Induced Oral Mucositis in Nasopharyngeal Carcinoma Patients: A Phase II Clinical Study - Lu Li MS; Yecai Huang MD; Jun Yin MD; Peng Xu MS; Mei Lan MD; Churong Li MS; Yunxiang Qi MD; Ke Xu MS; Bosen Li MS; Yukun Luo MS; Qinghua Jiang MS; Shanshan Peng MS; et al. (Integrative Cancer Therapies)
Purpose: Radiotherapy-induced oral mucositis is the most common side effect in nasopharyngeal carcinoma (NPC) patients. We aimed to evaluate the efficacy and safety of Rabdosia rubescens drop pills in NPC patients with radiation-induced oral mucositis (RTOM). Methods: The study involved 40 NPC patients who were given Rabdosia rubescens drop pills thrice daily from the start of radiation therapy. The study monitored the incidence and severity of oral mucositis and oral pain. The main outcomes measured were the occurrence rate of oral mucositis, grade 3 oral mucositis, oral pain assessment, and changes in immunological function, body weight, BMI, NRS2002, and albumin levels. Results: In the study, 38 patients completed the treatment. The incidence rates of Grade 0 to 3 oral mucositis were 5.26%, 21.05%, 47.37%, and 26.32% respectively. Pain levels were mild (42.11%), moderate (13.16%), and severe (13.16%). The onset of Grade 1, 2, and 3 oral mucositis occurred at 18, 24, and 30 days respectively. Grade 3 oral mucositis was associated with body weight, BMI, NRS2002 score, and albumin levels. Post-treatment, there was a decrease in CD4 + /CD8 + , CD3 + , and CD4 + immune cells, but an increase in CD8 + cells. Mild to moderate gastrointestinal adverse events were observed in 13.2% of patients. Conclusion: Rabdosia rubescens drop pills administration can reduce the incidence and severity of radiotherapy induced oral mucositis. Our finding suggested a positive impact of Rabdosia rubescens drops pills upon administration to NPC patients.